Unconscious Detection of One's Own Image. (April 2019) - Wójcik, Michał J.; Nowicka, Maria M.; Bola, Michał; Nowicka, Anna
A key mechanism behind preferential processing of self-related information might be an early and automatic capture of attention. Therefore, the present study tested a hypothesis that one's own face will attract bottom-up attention even without conscious identification. To test this, we used a dot-probe paradigm with electrophysiological recordings, in which participants ( N = 18) viewed masked and unmasked pairs of faces (other, self) presented laterally. Analysis of the sensitivity measure d  ′ indicated that faces were not consciously identified in the masked condition. A clear N2 posterior-contralateral (N2pc) component (a neural marker of attention shifts) was found in both the masked and unmasked conditions, revealing that one's own face automatically captures attention when processed unconsciously. Therefore, our study (a) demonstrates that self-related information is boosted at an early (preconscious) stage of processing, (b) identifies further features (beyond simple physical ones) that cause automatic attention capture, and (c) provides further evidence for the dissociative nature of attention and consciousness.